Body size affects individual winter foraging strategies of thick‐billed murres in the Bering Sea. (14th September 2015) - Orben, Rachael A.; Paredes, Rosana; Roby, Daniel D.; Irons, David B.; Shaffer, Scott A.; Gill, Jennifer
Summary Foraging and migration often require different energetic and movement strategies. Though not readily apparent, constraints during one phase might influence the foraging strategies observed in another. For marine birds that fly and dive, body size constraints likely present a trade‐off between foraging ability and migration as smaller bodies reduce flight costs, whereas larger bodies are advantageous for diving deeper. This study examines individual wintering strategies of deep diving thick‐billed murres (Uria lomvia) breeding at three colonies in the south‐eastern Bering Sea: St Paul, St George and Bogoslof. These colonies, arranged north to south, are located such that breeding birds forage in a gradient from shelf to deep‐water habitats. We used geolocation time‐depth recorders and stable isotopes from feathers to determine differences in foraging behaviour and diet of murres during three non‐breeding periods, 2008–2011. Body size was quantified by a principal component analysis (wing, culmen, head+bill and tarsus length). A hierarchical cluster analysis identified winter foraging strategies based on individual movement, diving behaviour and diet (inferred from stable isotopes). Structural body size differed by breeding island. Larger birds from St Paul had higher wing loading than smaller birds from St George. Larger birds, mainly from St Paul, dove to deeper depths, spent more time in the Bering Sea, and likely consumed higher trophic‐level prey in late winter. Three winter foraging strategies were identified. The main strategy, employed by small birds from all three breeding colonies in the first 2 years, was characterized by high residency areas in the North Pacific south of the Aleutians and nocturnal diving. In contrast, 31% of birds from St Paul remained in the Bering Sea and foraged mainly during the day, apparently feeding on higher trophic‐level prey. Throat feather stable isotopes indicated that individuals exhibited flexibility in the use of this colony‐specific foraging strategy. The third strategy only occurred in 2010/2011, when birds dove more and deeper, suggesting limited prey resources. Foraging strategies partitioned with respect to annual differences, presumably in response to shifts in distribution of prey, and were linked to body size. The presence of a colony‐specific wintering strategy suggests the potential for overwinter survival differences between these populations.